3D‐Printed, Carbon‐Nanotube‐Wrapped, Thermoresponsive Polymer Spheres for Safer Lithium‐Ion Batteries. Issue 9 (3rd July 2018) - Huang, Zhi Xiang; Sim, Glenn Joey; Tan, Jeck Chuang; Low, Hong Yee; Yang, Hui Ying
Abstract: Safety of lithium‐ion batteries (LIBs) has persistently plagued their development, despite widespread commercialization and usage. Thermal runaway is a notorious event where the overheating of the LIB results in a chain of events leading to the catastrophic failure of the device. Here, an in situ safety mechanism that shutdowns the LIB at critical temperatures before the onset of thermal runaway is developed. This is achieved by the deposition of thermal responsive polyethylene (PE) microspheres coated with multiwalled carbon nanotubes (CNTs) on electrodes via 3D printing. Rapid shutdown of LIB full cells under 60 s with ≈1 mg of additive is demonstrated. The mechanism of the shutdown is investigated through post‐mortem analysis of the heat‐treated cells that provides evidence of the formation of an insulating PE film that prevents ionic flow, disabling the LIB. Further, galvanostatic cycling of CNT‐coated PE‐loaded cells is used to demonstrate the advantages of the approach, where the precise and low loading of the conductive additive exhibits no impact on the full cell normal operation. Abstract : Safety first : The safety of lithium‐ion batteries (LIBs) has plagued their development, despite their widespread commercialization and usage. Thermal runaway is a notorious event where the overheating of the LIB results in a chain of events leading to the catastrophic failure of the device. An in situ safety mechanism that shutdowns the LIB at critical temperatures before the onset of thermal runaway is achieved by depositing thermal responsive polyethylene (PE) microspheres coated with multiwalled carbon nanotubes (CNTs) on electrodes via 3D printing.